TAḤLĪL AHDĀF AT-TA‘LĪM (TP) WA SĀ’IR AHDĀF AT-TA‘LĪM (ATP) LIMĀDDAH AL-LUGAH AL-‘ARABIYYAH WIFQA MANHAJ AT-TA‘LĪM AL-MUSTAQIL - nuriatul maftukhah; Farah Diana Manzilah; Muhammad Syaifuddin Zuhri; Abul Ma'ali (Universitas Negeri Semarang, 2023)
مستخلص البحث تطوير المنهج بشكل مستمر أمر لا مفر منه وذلك لقصور المنهج عن تلبية حاجات المتعلمين واهتماماتهم أو حاجات المجتمع وأهدافهم بسبب التغيير الذي يطرأ على المتعلم وبيئته ومجتمعه. لقد قررت وزارة التربية والتعليم والثقافة بإندونيسيا بتغيير منهج 2013 بمنهج التعليم المستقل بشكل تدريجي. من المدرسة التي طبقت المنهج المستقل المدرسة الثانوية الإسلامية الحكومية ١ لامونجان. الغرض من هذه الدراسة هو معرفة مدى قدرة المدرسة في ترجمة أهداف التعليم وسير أهداف التعليم لمادة اللغة العربية للمنهج المستقل المرسومة من قبل الوزارة في أرض الواقع. استخدم الباحثون هذا البحث المدخل الكيفي بنوع الدراسة المكتبية، حيث قام الباحث بتحليل أهداف التعليم وسير أهداف تعليم اللغة العربية في المدرسة الثانوية الإسلامية الحكومية ١ لامونجان كمصدر أساسي للبيانات، وكذلك الكتب والمقالات والمجلات والمراجع المتعلقة بهذا البحث كمصادر بيانات الثانوية. استخدم الباحثون أساليب التوثيق في جمع البيانات، وتقنيات تحليل المحتوى. أما نتائج البحث: أن الأهداف التعليمية استوفت المكونات القياسية التي قررتها الحكومة من حيث الكفاءات والمحتوى. كما حقق سير أهداف التعليم جميع المكونات للمنهج المستقل سواء أكانت مكونات الكفاءة، ونتائج التعليم، والمحتوى، والتنويع، وأهداف التعليم ومراحل التعليم. من معوقات تنفيذ المنهج المستقل التي تعرقل المعلم هي تحديد تسلسل المراحل في جزء من الكفاءة المعنية. وخلاصة هذه الدراسة أن أهداف التعليم وسير أهداف تعليم اللغة العربية يمكن تطبيقها في مادة اللغة العربية في المرحلة الثانوية. الكلمات المفتاحية: المناهج المستقلة، أهداف التعليم، سير أهداف التعليم Abstract Sustainable curriculum development is inevitable because the curriculum fails to meet the needs and interests of learners or the needs and goals of society due to changes that occur in students, the environment and society. The Ministry of Education and Culture of the Republic of Indonesia has decided to gradually change the 2013 curriculum to an independent curriculum. One of the schools that implements an independent curriculum is SMA Islam Negeri 1 Lamongan. The purpose of this study is to know the extent of the school's ability to translate the educational objectives and the progress of the educational objectives of the Arabic language subject to the independent curriculum drawn by the Ministry on the field. Researchers use a qualitative approach with a literature review method. Learning Objectives and Flow of Arabic Learning Objectives in MAN 1 Lamongan as a primary data source and books, articles, journals, and references related to this research need as secondary data sources. The author uses documentation methods in data collection, and content analyst techniques. The results of research for educational purposes are that they have met the standard components applied by the government, namely containing competencies and content. The Learning Objectives Flow component has also fulfilled all components in the independent curriculum. Both in the components of competence, learning outcomes, content, variations, learning objectives and phases in learning have been fulfilled. Thereare flaws in the numbering in phases in each competency. As a result, it creates confusion for educators in determining the sequence of phases in the part of the competence in question. The conclusion of this study is that the educational objectives and the flow of Arabic language education objectives can be applied in Arabic subjects at the upper secondary level. Keywords: Independent Curriculum, Learning Objectives, Flow of Learning Objectives